Introducing a Formula for Obtaining the Total Deviation Index in Aging Studies - Andisheh Bakhshi; Enayatollah Bakhshi (University of Social Welfare & Rehabilitation Sciences, 2020)
Objectives: Since the study on the elderly people and recording related data requires more accuracy, the calculation of measurement error is very important. This study aims to introduce a simple formula to obtain and interpret the Total Deviation Index (TDI) and encourage researchers to use it as a suitable tool to determine the reliability in psychometrics studies.  Methods & Materials:  In this cross-sectional study conducted in 2019, participants were 105 older adults living in Tehran, Iran. The 36-Item Short Form Health Survey (SF-36) questionnaire was completed by them within two weeks. The Intraclass Correlation Coefficient (ICC) and TDI values were calculated and compared for each subscale of the SF-36. Results: The lowest TDI value belonged to the "physical functioning" subscale, while the "emotional problems" subscale had the highest TDI value. At a 95% confidence interval, the maximum measurement errors in physical functioning and emotional problems were reported 22 and 34 (out of 100), respectively.  Conclusion: Since the ICC cannot determine how much of the difference in the subscale scores is related to the measurement error, and given the simple interpretation of the TDI, it is recommended that researchers use the proposed formula and obtain the TDI value for the reliability in psychometrics studies.